Effects of additional Vitamin E and selenium supply on G6PDH activity in rats treated with high doses of glucocorticoid - Yilmaz, S; Beytut, E; Erisir, M; Ozan, S; Aksakal, M (Elsevier Ireland Ltd, 2006)
The aim of this work was to determine the effects of dietary intake Vitamin E and selenium (Se) on glucose-6-phosphate dehydrogenase (G6PDH) activity in rats treated with high doses of prednisolone. Two hundred and fifty adult male Wister rats were randomly divided into five groups. The rats were fed a normal diet, but groups 3, 4, and 5 received a daily supplement in their drinking water of 20 mg Vitamin E. 0.3 mg Se, and a combination of Vitamin E and Se, respectively, for 30 days. For 3 days subsequently, the control group (group 1) was treated with a placebo, and the remaining four groups were injected intramuscularly with 100 mg/kg body weight prednisolone. After the last administration of prednisolone, 10 rats from each group were killed at 4, 8, 12, 24, and 48 h and the activities of G6PDH enzymes in their tissues were measured. Hepatic and spleen G6PDH activities in the prednisolone treatment group began to decrease gradually at 8 h, while enzyme activities did not change in the kidney and heart. However, the administration of Vitamin E alone did not affect G6PDH activity in any of the tissues. Se supplementation had a preventive effect on the decrease of G6PDH caused by prednisolone and improved the diminished activities of G6PDH. Therefore, the present study demonstrates that a high dose of prednisolone may alter the effects of normal dose glucocorticoids and that Se is effective in reducing damage in prednisolone-treated rats: Se may prevent the changes in G6PDH activity in various tissues caused by prednisolone in various tissues. (c) 2005 Published by Elsevier Ireland Ltd.
Keywords: high dose of glucocorticoid; Vitamin E; selenium; glucose-6-phosphate dehydrogenase